Gene gain and loss push prokaryotes beyond the homologous recombination barrier and accelerate genome sequence divergence - Jaime Iranzo (Nature Portfolio, 2019)
A significant proportion of the molecular evolution of bacteria and archaea occurs through gene gain and loss. Here Iranzo et al. develop a mathematical model that explains observed differential patterns of sequence evolution vs. gene content evolution as a consequence of homologous recombination.